The application status quo of tools for assessing delirium at home and abroad (国内外谵妄量表的应用现状分析) - XIAO Tingting (肖婷婷) (Association of Integrative Nursing, 2022)
There has been an increasing incidence of delirium which causing long-term consequences of life. This paper summarized the application status quo of tools for assessing delirium at home and abroad, in order to provide reference for standardized evaluation and precise treatment of delirium. (谵妄在临床发生率高, 远期不良后果严重。本研究就目前国内外谵妄工具的使用情况进行总结和分析, 以期为进一步标准化、精准化谵妄评估到治疗提供依据。)